2018
DOI: 10.1103/physrevb.97.014519
|View full text |Cite
|
Sign up to set email alerts
|

Fulde-Ferrell state in a ferromagnetic chiral superconductor with magnetic domain walls

Abstract: Motivated by the recent theoretical and experimental progress in the heavy fermion system UCoGe, we study ferromagnetic chiral superconductors in the presence of magnetic domains. Within mean field approximations, it is shown that chiral superconducting domains are naturally induced by the ferromagnetic domains. The domain wall current flows in the opposite direction to the naively expected one as in 3 He-A phase due to contributions from "unpaired electrons". Consequently, the domain wall current flows in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In addition to the SIV scenario, an interesting scenario to explain the non-SC fraction is the presence of unpaired electrons related to the spontaneous charge current resulting from the FM chiral SC state [40]. The scanning SQUID measurement revealed that the FM domain wall width is ∼ 0.1-1 nm, and the size of the FM domains, an order of 10 µm, shows no large change across the SC transition [41].…”
mentioning
confidence: 99%
“…In addition to the SIV scenario, an interesting scenario to explain the non-SC fraction is the presence of unpaired electrons related to the spontaneous charge current resulting from the FM chiral SC state [40]. The scanning SQUID measurement revealed that the FM domain wall width is ∼ 0.1-1 nm, and the size of the FM domains, an order of 10 µm, shows no large change across the SC transition [41].…”
mentioning
confidence: 99%
“…Since the scaling contribution ∂Ψ(L/l B )/∂L = Ψ (L/l B )/l B will depend on the magnetic field B = l −2 B , the Casimir force can be controlled by B, leading to a possible sample volume change. In a confined or restricted geometry with surfaces corresponding to a real material, a finite size induced phase transition may also occur 77,78 as in a superconducting system [79][80][81] . Similarly, a temperature change in an adiabatic setup may be caused by a magnetic field in a critical Dirac system at finite temperature, where the free energy density will have a scaling form F (g = 0, l −1 B , L −1 τ ) = F 0 + Ψ(L τ /l B )/L D τ with temperature T = 1/L τ .…”
Section: Discussion and Summarymentioning
confidence: 99%